Lactobacillus reuteri promotes Helicobacter hepaticus-associated typhlocolitis in gnotobiotic B6.129P2-IL-10(tm1Cgn) (IL-10(−/−)) mice - Whary, Mark T (Blackwell Science Inc, 2011)
To model inflammatory bowel disease, we assessed infection with Helicobacter hepaticus 3B1 (ATCC 51449) and a potential probiotic Lactobacillus reuteri (ATCC PTA-6475) in gnotobiotic B6.129P2-IL-10(tm1Cgn) (IL-10(−/−)) mice. No typhlocolitis developed in germ-free controls (n = 21) or in L. reuteri (n = 8) or H. hepaticus (n = 18) mono-associated mice for 20 weeks post-infection. As positive controls, three specific pathogen-free IL-10(−/−) mice dosed with H. hepaticus developed severe typhlocolitis within 11 weeks. Because L. reuteri PTA-6475 has anti-inflammatory properties in vitro, it was unexpected to observe significant typhlocolitis (P < 0·0001) in mice that had been infected with L. reuteri followed in 1 week by H. hepaticus (n = 16). The H. hepaticus colonization was not affected through 20 weeks post-infection but L. reuteri colonization was lower in co-infected compared with L. reuteri mono-associated mice at 8–11 weeks post-infection (P < 0·05). Typhlocolitis was associated with an increased T helper type 1 serum IgG2c response to H. hepaticus in co-infected mice compared with H. hepaticus mono-associated mice (P < 0·005) and similarly, mRNA expression in caecal–colonic tissue was elevated at least twofold for chemokine ligands and pro-inflammatory interleukin-1α (IL-1α), IL-1β, IL-12 receptor, tumour necrosis factor-α and inducible nitric oxide synthase. Anti-inflammatory transforming growth factor-β, lactotransferrin, peptidoglycan recognition proteins, Toll-like receptors 4, 6, 8 and particularly 9 gene expression, were also elevated only in co-infected mice (P < 0·05). These data support that the development of typhlocolitis in H. hepaticus-infected IL-10(−/−) mice required co-colonization with other microbiota and in this study, required only L. reuteri. Although the effects other microbiota may have on H. hepaticus virulence properties remain speculative, further investigations using this gnotobiotic model are now possible.